New Anticancer Drugs: Reliably Assessing "Value" While Addressing High Prices. - Stewart, David J.; Bradford, John-Peter; Sehdev, Sandeep; Ramsay, Tim; Navani, Vishal; Rawson, Nigel S. B.; Jiang, Di Maria; Gotfrit, Joanna; Wheatley-Price, Paul; Liu, Geoffrey; Kaplan, Alan; Spadafora, Silvana; et al. (Current Oncology, 2024)
Countries face challenges in paying for new drugs. High prices are driven in part by exploding drug development costs, which, in turn, are driven by essential but excessive regulation. Burdensome regulation also delays drug development, and this can translate into thousands of life-years lost. We need system-wide reform that will enable less expensive, faster drug development. The speed with which COVID-19 vaccines and AIDS therapies were developed indicates this is possible if governments prioritize it. Countries also differ in how they value drugs, and generally, those willing to pay more have better, faster access. Canada is used as an example to illustrate how "incremental cost-effectiveness ratios" (ICERs) based on measures such as gains in "quality-adjusted life-years" (QALYs) may be used to determine a drug's value but are often problematic, imprecise assessments. Generally, ICER/QALY estimates inadequately consider the impact of patient crossover or long post-progression survival, therapy benefits in distinct subpopulations, positive impacts of the therapy on other healthcare or societal costs, how much governments willingly might pay for other things, etc. Furthermore, a QALY value should be higher for a lethal or uncommon disease than for a common, nonlethal disease. Compared to international comparators, Canada is particularly ineffective in initiating public funding for essential new medications. Addressing these disparities demands urgent reform.